2000
DOI: 10.4049/jimmunol.164.12.6647
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Sulfamethoxazole and Its Reactive Metabolites by Drug-Specific CD4+ T Cells from Allergic Individuals

Abstract: The recognition of the antibiotic sulfamethoxazole (SMX) by T cells is usually explained with the hapten-carrier model. However, recent investigations have revealed a MHC-restricted but processing- and metabolism-independent pathway of drug presentation. This suggested a labile, low-affinity binding of SMX to MHC-peptide complexes on APC. To study the role of covalent vs noncovalent drug presentation in SMX allergy, we analyzed the proliferative response of PBMC and T cell clones from patients with SMX allergy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
206
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 200 publications
(229 citation statements)
references
References 24 publications
(20 reference statements)
21
206
1
1
Order By: Relevance
“…In some cases there may be haptenization of self-peptides by a reactive metabolite, but it has been demonstrated that medications are often presented through noncovalent binding with MHC Class I molecules. 15 In this context, one may hypothesize that rare and severe reactions to drugs, such as SJS or TEN are dependent on infrequent HLA alleles, each being capable of binding to a 'specific' drug.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases there may be haptenization of self-peptides by a reactive metabolite, but it has been demonstrated that medications are often presented through noncovalent binding with MHC Class I molecules. 15 In this context, one may hypothesize that rare and severe reactions to drugs, such as SJS or TEN are dependent on infrequent HLA alleles, each being capable of binding to a 'specific' drug.…”
Section: Resultsmentioning
confidence: 99%
“…While much remains to be learned about the mechanisms of the varied reactions that can occur in the skin after systemic drug administration, many of these reactions are consistent with delayed-type hypersensitivity -implicating the involvement of the immune system in their provocation (Cribb et al, 1996a;Svensson et al, 2001;Pichler et al, 2002;Pichler, 2003). The observation that patients with a history of such reactions may possess drug-reactive T-cells suggests that these responses are T-cell mediated (Mauri-Hellweg et al, 1995;Schnyder et al, 2000;Nassif et al, 2002). As drugs noted to provoke these reactions are small molecules, it has been proposed that bioactivation of drugs to reactive metabolites is an essential prerequisite to the initiation of CDRs (Park and Kitteringham, 1990;Park et al, 1998;Park et al, 2000;Svensson, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…RNeasy 96 total RNA extraction kit and RLT lysis buffer were obtained from Qiagen. Oligo(dT) [12][13][14][15][16][17][18] primer, 2Ј-deoxynucleoside 5Ј-triphosphate mix and the Superscript II reverse transcriptase kit were obtained from Invitrogen Life Technologies. Oligonucleotide fluorogenic probes and TaqMan Universal PCR Mastermix were obtained from Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%